A comprehensive review on the use of nano-fluids and nano-PCM in parabolic trough solar collectors (PTC). (June 2022) - Nawsud, Zakaria Alimohammadi; Altouni, Armin; Akhijahani, Hadi Samimi; Kargarsharifabad, Hadi
Highlights: Using nano-fluids and nano-PCMs improved heat transfer coefficient, outlet temperature, energetic and exergetic efficiency of PTCs. Using modified absorbers in the focal line increases the thermal performance of PTCs. The Size of nano-particles at the range of 40–100 nm and concentration at the range of 4–9% promotes the thermal performance of PTC. Computational fluid dynamics is an efficient method for thermal analysis and optimization. The quality of dried products with the solar dryer assisted with PTC improved. Abstract: In the present study, a review is conducted on the state-of-the-art research on the potential of nano-fluids in parabolic trough collectors (PTCs) in solar thermal systems. PTCs are one of the most used collectors in applications such as desalination, drying processes, heating and cooling loops, and power generation plant. Despite the plausible thermal performance of the PTCs the thermal efficiency of such systems is low. Hence, much effort has been performed to promote the energy and exergy efficiency of PTCs. PTCs typically work with working fluid and usually to get the better performance nano-fluids are used. Various parameters affect on the efficiency of PTCs. Beside the fluid flow rate, other parameters including volume fraction, type of the base fluid, type of the nanomaterial, size, and morphology affected on the performance of the system. Hence, in the present work, an attempt has been made to deep review of the latest studies conducted on the effect of the mentioned parameters of nano-fluid on the thermal performance of PTCs. Moreover the effect of using PCM and nano-PCM on the thermal performance of the solar systems were reviewed.